British Literary Responses to the Suez Crisis. Issue 2 (November 2013) - Hammond, Andrew
By the 1950s, the Suez Canal was crucial for Britain's trade in the Middle East, for its communication with overseas dependencies and for its containment of Soviet influence in Africa. The sudden nationalisation of the canal in July 1956 by Gamal Abdul Nasser, and the obstruction of British military intercession by the United States, struck a blow to the prestige of the nation that resonated in the work of British novelists for decades to come. This essay examines the discursive responses to the Suez Crisis in such texts as John Fowles' Daniel Martin (1977), Lawrence Durrell's The Alexandria Quartet (1957–60) and Olivia Manning's The Levant Trilogy (1977–80), analysing its links to orientalism, anti-Americanism, Cold War hostilities and fears about British national decline.